Increased epithelial uptake of protein antigens in the ileum of Crohn's disease mediated by tumour necrosis factor α. Issue 12 (11th November 2004) - Söderholm, J D; Streutker, C; Yang, P-C; Paterson, C; Singh, P K; McKay, D M; Sherman, P M; Croitoru, K; Perdue, M H
Abstract : Background and aims: The exact nature of the epithelial barrier defect in Crohn's disease remains to be elucidated. Previously we showed increased permeability to proteins in ileal Crohn's disease. Our aims were to study if this barrier defect (a) involves endocytotic uptake of antigens and (b) is related to low grade inflammation not detectable by histology. Methods: Macroscopically normal segments of distal ileum of Crohn's disease patients (n = 10) were subgrouped into non-inflamed (histologically unaffected) and slightly inflamed tissues and studied in Ussing chambers, with normal ileal specimens from colon cancer patients (n = 9) as controls. Endocytotic uptake into enterocytes of the protein antigen horseradish peroxidase was assessed by measuring the area of horseradish peroxidase containing endosomes in electron photomicrographs. Mucosal tumour necrosis factor α (TNF-α) mRNA was quantified using real time polymerase chain reaction. For comparison, the effects of low doses of TNF-α on endosomal uptake of horseradish peroxidase were studied in cultured T84 cells grown on filter supports. Results: The area of horseradish peroxidase containing endosomes was increased (p<0.001) in enterocytes of non-inflamed ileum of Crohn's disease (2.8 (0.7) μm 2 /300 μm 2 ) compared with control ileum (0.6 (0.06)). In non-inflamed mucosa, a significant association between endosomal uptake and mucosal expression of TNF-α mRNA (p = 0.03) was found. Low concentrations of TNF-α (0.25–1.0 ng/ml) enhanced the endosomal uptake of horseradish peroxidase in polarised T84 cells, without affecting transepithelial electrical resistance. Conclusions: Our findings suggest increased endosomal uptake of antigens in ileal Crohn's disease that may be mediated by TNF-α. These data highlight the transcellular route of antigen uptake in barrier dysfunction and implicate the interaction between epithelial cells and the innate immune system in the development of mucosal inflammation.